Colonial Nature of Public Education as a Factor of Ethnical Deformation. / La naturaleza colonial de la educación pública como factor de deformación étnica - Tursun, Khazretali M.; As, Hakan; Bazarbaev, Kanat K.; Rezhep, Aral; Kelesh, Murat (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The paper deals with the historical analysis of the reforms in the public education in the last period of the Russian colonization of the Central Asian states. Authors defined that the policy implemented by Russia in this region was marked by the rigid colonial governance. The modernization policy of the empire was defined as factor of ethnical deformation. The paper contains the assessment of the cultural-educational activities of jadidism,which in its activities based on the rich cultural traditions of the local population and governed by the achievements of the European civilization, emerged as an alternative to the policy of the colonial authorities'public education.RESUMEN El documento trata sobre el análisis histórico de las reformas de la educación pública en el último período de la colonización rusa de los estados de Asia Central. Los autores definieron que la política implementada por Rusia en esta región estaba marcada por el rígido gobierno colonial. La política de modernización del imperio se definió como factor de deformación étnica. El documento contiene la evaluación de las actividades culturales y educativas del jadidismo, que en sus actividades basadas en las ricas tradiciones culturales de la población local, y regidas por los logros de la civilización Europea, surgió como una alternativa a la política de educación pública de las autoridades coloniales.